2013
DOI: 10.1159/000353172
|View full text |Cite
|
Sign up to set email alerts
|

Ground Night Nesting in Chimpanzees: New Insights from Central Chimpanzees (Pan troglodytes troglodytes) in South-East Cameroon

Abstract: Some chimpanzee populations exhibit ground night nesting, which occurs in different habitat types, is driven by a variety of interconnected factors, and may reflect cultural or social differences. This has important implications for ape conservation management, given that accurate nest builder identification is required to estimate density, crucial in monitoring, and allows inferences about environmental and social factors that may have contributed to the transition from tree to ground sleeping in early homini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 66 publications
(157 reference statements)
2
59
2
Order By: Relevance
“…However, our results are not consistent with these observations. Our seasonal analysis revealed a significant increase in swamp use by chimpanzees in the long dry season, as observed elsewhere (Morgan et al, ; Poulsen & Clark, ) and in the same site in a previous study (Tagg, Willie, Petre, & Haggis, ). We found gorillas to randomly use LG and YSF in all seasons, except in the long rainy season when they used YSF in proportion significantly less than would be expected by chance; however, a general analysis revealed that gorillas preferred LG, but again used YSF in proportion significantly less than would be expected by chance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results are not consistent with these observations. Our seasonal analysis revealed a significant increase in swamp use by chimpanzees in the long dry season, as observed elsewhere (Morgan et al, ; Poulsen & Clark, ) and in the same site in a previous study (Tagg, Willie, Petre, & Haggis, ). We found gorillas to randomly use LG and YSF in all seasons, except in the long rainy season when they used YSF in proportion significantly less than would be expected by chance; however, a general analysis revealed that gorillas preferred LG, but again used YSF in proportion significantly less than would be expected by chance.…”
Section: Discussionsupporting
confidence: 90%
“…fruits in swamps in the long dry season, competition between gorillas and chimpanzees may be avoided in swamps by the increasing consumption of herbs by gorillas in the long dry season. Meanwhile, it has been found that herbaceous plants suitable for gorilla nest building are less abundant in mature forest than in old secondary forest in this region (Willie et al, ), while chimpanzee nesting trees are less abundant in young secondary forest than in mature forest (Tagg et al, ). Adding to the lower abundance of chimpanzee preferred fruiting plants in young secondary forest found in this study, this observation may explain the near absence of gorillas and chimpanzees in MF and in YSF, respectively, in all seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some large‐bodied primates sleep terrestrially on bare ground or on cliffs, such as group‐sleeping baboons ( Papio spp.) (Hamilton, ), or individually sleeping great apes (Fruth & Hohmann, ; Tagg, Willie, Petre, & Haggis, ). Of particular interest in the study of primate sleep is nest‐building behavior, which has evolved independently six to eight times in primates (Kappeler, ).…”
Section: Primate Sleeping Sitesmentioning
confidence: 99%
“…Nest building is a habitual behavior in great apes, constructions are built for short periods only and never serve as a shelter for caching young. Structures are commonly built within trees, although ground nests built with terrestrial vegetation are common in gorilla and ground‐nesting is likely present at low rates across all species and subspecies (Tagg et al, ). These structures attracted the attention of early explorers such as Du Chaillu (), Hornaday (), and Savage and Wyman (1843–1844).…”
Section: Primate Sleeping Sitesmentioning
confidence: 99%
“…Herbaceous plants also provide fallback foods for chimpanzees (Harrison & Marshall, 2011). In addition, chimpanzees occasionally sleep in ground nests built using herbaceous plants (Koops, Humle, Sterck, & Matsuzawa, 2007;Tagg, Willie, Petre, & Haggis, 2013). Both chimpanzees and bonobos frequently utilize plant materials, including herbaceous species, to make tools to extract termites from termite nests (Deblauwe, Guislain, Dupain, & Van Elsacker, 2006;McGrew et al, 2007;Sanz & Morgan, 2007).…”
mentioning
confidence: 99%